2021
DOI: 10.1103/physrevapplied.16.044064
|View full text |Cite
|
Sign up to set email alerts
|

Optical Brewster Metasurfaces Exhibiting Ultrabroadband Reflectionless Absorption and Extreme Angular Asymmetry

Abstract: If it is the author's pre-published version, changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please refer to the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The simulation and experimental results demonstrate successful control of the amplitude, wave front, and polarization. The capability to arbitrarily engineer the anisotropic complex surface conductivity of our proposed metasurface also makes it a promising candidate for functionalities with strong angular asymmetry [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The simulation and experimental results demonstrate successful control of the amplitude, wave front, and polarization. The capability to arbitrarily engineer the anisotropic complex surface conductivity of our proposed metasurface also makes it a promising candidate for functionalities with strong angular asymmetry [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Hereafter, we refer to a singlelayer metamaterial with finite thickness as a metafilm. So far, the Brewster effect has been investigated in various kinds of metamaterials and metasurfaces [22][23][24][25][26][27][28][29]. As a part of these studies, we showed in our previous papers [30,31] that reflection in a metafilm can be completely suppressed by arranging the meta-atoms so that the oscillation direction of the electric dipole (or magnetic dipole) induced in the meta-atoms coincides with the propagation direction of the reflected wave.…”
Section: Introductionmentioning
confidence: 98%
“…In [23], a coherent asymmetric absorber using space-modulated metasurface was theoretically proposed, which behaves as an absorber or as a retro-reflector depending on the angle of incidence by two coherent waves. Three dimensional asymmetric meta-gratings were applied for angularasymmetric transmissions [24]- [25]. Based on the anomalous Brewster effect, a transition between perfect transparency and perfect absorption was achieved under 55.6° and −55.6° oblique incidences [24].…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensional asymmetric meta-gratings were applied for angularasymmetric transmissions [24]- [25]. Based on the anomalous Brewster effect, a transition between perfect transparency and perfect absorption was achieved under 55.6° and −55.6° oblique incidences [24]. Similar meta-grating structure was also used to realize a Janus backscattering mirror that retro-reflects incident waves for one side while showing transparency in the time-reversed reflection channel [25].…”
Section: Introductionmentioning
confidence: 99%